Castleman Disease Mimicking Neurogenic Tumor Radiologically: A Case Report - Haitham Akaash, Fatima Shahid, Nousheen Qureshi, Nayer Ayub, Asmara Hussain, Sundas Masood (Journal of Rawalpindi Medical College, 2021)
Background: There are only few case reports of enlarged lymph node affecting carotid artery and mimicking neurogenic tumor radiologically. We have one such report to present Case presentation: We presented a young male with mass in left upper part of neck mimicking carotid body tumor on CT scan and MRI. Post operatively histopathology sample was sent which was identified as a case of castleman disease. This case has been described in detail in our report. Conclusion: Mass that was initially misunderstood as a case of neurogenic tumor and prepared accordingly showed out to a case of castleman lymphadenopathy. Thus the diagnosis of such unique presentation was made Due to castleman disease rarity and mostly asymptomatic presentation it is difficult to diagnose. Its similarity to lymphoma and paraganglioma radiologically further adds to its difficulty in diagnosis.. Thus it is important to consider castleman disease as a differential diagnosis of such mass.